To find the equation of a line that is perpendicular to another line and shares the same y-intercept, we first need to find the slope of the line that passes through the given points \((0, 4)\) and \((-8, 0)\).
-
Calculate the slope (m) of the line through the points: \[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{0 - 4}{-8 - 0} = \frac{-4}{-8} = \frac{1}{2} \]
-
Determine the slope of the perpendicular line: The slope of a line that is perpendicular to another line is the negative reciprocal of the original slope. Thus, \[ m_{\text{perpendicular}} = -\frac{1}{m} = -\frac{1}{\frac{1}{2}} = -2 \]
-
Equation of the perpendicular line: Since the new line shares the same y-intercept as the line through the points, and the y-intercept from the point \((0, 4)\) is \(4\), we can write the equation in slope-intercept form \(y = mx + b\) using the slope we found and the y-intercept: \[ y = -2x + 4 \]
Therefore, the equation of the line that is perpendicular to the original line and shares the same y-intercept is:
\[ \boxed{y = -2x + 4} \]